The Impact of Gorilla Marketing on Mental Image`s Dimensions of the Organization: An Application on Cairo Greater Area Small and Medium Industrial Projects - Bakhit, Amany (The Arab Journal of Administration, 2024)
The study aims to reach the relationship between gorilla marketing (viral , ambush, Ambient, buzz Marketing), and the emotional dimensions (cognitive, affective, and behavioral) of small and medium (SM) industrial projects. Data used for the study were some available secondary data and on responses to a questionnaire. Respondents were 326 managers and owners of some SM projects in Cairo Greater Area (Cairo, Giza and Kaloubia), response rate was 71,47% A inferential statistics approach was used for the analysis of responses to questionnaire items; MANOVA , multiple regression and path analysis techniques were used to reach the direct and indirect relationships between the studied variables. Results showed a significant relationship between gorilla components and the mental image`s (cognitive, affective, and behavioral) dimensions for SM projects; where gorilla components explain 73.8% of the variability of the cognitive dimension; 68.9% of the cognitive dimension and 57.1% of the behavioral dimension. The Viral Gorilla marketing components ranked first to affect the mental image dimensions (89.3%, 81.5% and 72.2% for cognitive, affective, and behavioral dimensions, respectively; ambush marketing was ranked second; followed by ambient marketing and buzz marketing was ranked last. All Gorilla marketing components have an impact on the cognitive and affective dimensions (at the 5% level of significance), however, ambient marketing has no impact on the behavioral dimension.